On the synchrotron radiation in curved magnetic lines - Sobolev, Ya.M. (Кинематика и физика небесных тел, 2005)
The general formulae that describe radiation of an ultrarelativistic electron moving along spiral trajectories with a small pitch angle in curved magnetic force lines are considered. These formulae can be identical to either synchrotron radiation or curvature radiation in certain parametric regions, but there are appreciable differences between new and old mechanisms when the velocity of Larmor’s rotation is of the order of a centrifugal drift velocity. The case when the Larmor velocity is equal exactly to the velocity of centrifugal drift was not investigated earlier. There are points with zero curvature in the particle’s trajectory, in that case. The spectral angular distribution, polarization characteristics in the neighborhood of these points have been obtained.